2009
DOI: 10.1038/emboj.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic removal of diacylglycerol by DGKζ and PSD-95 regulates dendritic spine maintenance

Abstract: Diacylglycerol (DAG) is an important lipid signalling molecule that exerts an effect on various effector proteins including protein kinase C. A main mechanism for DAG removal is to convert it to phosphatidic acid (PA) by DAG kinases (DGKs). However, it is not well understood how DGKs are targeted to specific subcellular sites and tightly regulates DAG levels. The neuronal synapse is a prominent site of DAG production. Here, we show that DGKf is targeted to excitatory synapses through its direct interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 58 publications
1
70
1
Order By: Relevance
“…In hippocampal slices of DGKzKO mice, PA production has also been found to decrease after stimula tion, and the spine density of hippocampal CA1 pyrami dal neurons are significantly reduced, suggesting that DGKz is required to maintain dendritic spines (30). Furthermore, Schaffer collateralCA1 pyramidal syn apses in the hippocampus of DGKzKO mice showed enhanced longterm potentiation (LTP) and attenuated longterm depression (LTD) (70).…”
Section: Dgkzmentioning
confidence: 95%
See 2 more Smart Citations
“…In hippocampal slices of DGKzKO mice, PA production has also been found to decrease after stimula tion, and the spine density of hippocampal CA1 pyrami dal neurons are significantly reduced, suggesting that DGKz is required to maintain dendritic spines (30). Furthermore, Schaffer collateralCA1 pyramidal syn apses in the hippocampus of DGKzKO mice showed enhanced longterm potentiation (LTP) and attenuated longterm depression (LTD) (70).…”
Section: Dgkzmentioning
confidence: 95%
“…Furthermore, Schaffer collateralCA1 pyramidal syn apses in the hippocampus of DGKzKO mice showed enhanced longterm potentiation (LTP) and attenuated longterm depression (LTD) (70). In dendric spine main tenance, DGKz also plays an important role by not only affecting the PA production, but also interacting or forming a multiprotein complex with PSD95, p21 activated kinase 1 (PAK1), RASrelated C3 botulinus toxin substrate 1 (Rac1), and others (30,71). However, the behavioral analysis of cognitive function or other higher brain functions has not yet been reported and therefore, further research is needed to confirm DGKz's involvement in brain function.…”
Section: Dgkzmentioning
confidence: 99%
See 1 more Smart Citation
“…Dgkκ is a member of the DGK isozymes, master regulators of the balance between DAG and PA signaling (31). Several DGKs have been shown to be involved in structural and synaptic plasticity control (33)(34)(35)(36), but no data were available on Dgkκ neuronal function. We identified that the absence of FMRP leads to the deregulation of mGluRIdependent DGK activity, causing perturbations in the balance between its substrate, DAG, and its product, PA.…”
Section: Discussionmentioning
confidence: 99%
“…Multivalent scaffold molecules that link transmembrane proteins to the cytoskeleton are candidate determinants of synapse stability. Recent studies imply a stabilizing role for Postsynaptic density protein-95 (PSD-95), a principal vertebrate synaptic scaffold protein, during activity-dependent maturation of glutamatergic synapses (Ehrlich et al, 2007;Steiner et al, 2008;Kim et al, 2009). The linkage of PSD-95 to ionotropic glutamate receptors (GluRs), however, makes it difficult to assess a direct involvement in synaptic structural integrity independent from activity-related effects.…”
Section: Introductionmentioning
confidence: 99%